Pengaruh Literasi Digital Terhadap Etika Bermedia Sosial di MTs Miftahul Ulum Pangkalan Balai - Ismarani Junia Putri; izzatuzzahroh; Hartatiana; Muhammad Win Afgani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the influence of digital literacy on social media ethics among students at MTs Miftahul Ulum Pangkalan Balai. The background of the study is based on the increasing use of social media among madrasah teenagers, which is not always accompanied by adequate digital literacy skills and ethical awareness. The study uses a quantitative approach with associative research to measure the relationship between digital literacy (X) and social media ethics (Y). Data were collected through a questionnaire with a three-level Likert scale given to 54 students, along with supporting observations. Data analysis was conducted using descriptive statistics and a simple linear regression test with a significance level of 0.05. The results of the study indicate that students' digital literacy levels are in the high category, especially in information access, digital ethics, and data security, although information evaluation skills still need to be improved. Social media ethics